Pengaruh Harga, Kualitas Produk Dan Kualitas Pelayanan Terhadap Minat Beli Konsumen (Studi Kasus pada Konsumen Geprek Kak Rose Tlogomas Kota Malang) - Subhan Riadi; Agus Widarko; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims the effect of of price, product quality and service quality on the buying interest of Geprek Kak Rose Tlogomas consumers. The dependent variable in this study is consumer buying interest, and there are 3 (three) independent variables namely price, product quality and service quality. The type of research used in this research is explanatory research with a quantitative approach method. This research data collection method using a questionnaire. The population in this study were 630 consumers of Geprek Kak Rose Tlogomas. The sampling technique was calculated using the slovin formula and a total sample of 86 respondents was obtained. This research data collection method using a questionnaire. The data analysis technique used in this study is multiple linear regression, instrument test, normality test, classical assumption test, F test, t test, and coefficient of determination test using SPSS ver. software. 26.0. The results of the study show that price, product quality and service quality simultaneously affect consumer buying interest. Partially, prices affect consumer buying interest. Product quality affects consumer buying interest. Service quality affects consumer buying interest. From the results of testing the coefficient of determination of the independent variables Price, product quality, and service quality are able to explain the consumer buying interest variable, which is equal to 49.5%. While the other 50.5% is measured or influenced by other variables not examined in this study such as product attributes, customer satisfaction, brand preference, perceived value and physical environment. Keywords: Consumer Buying Interest, Price, Product Quality, Service Quality